2019
DOI: 10.3389/fpsyt.2019.00830
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs4680 COMT, rs6280 DRD3, and rs7322347 5HT2A With Clinical Features of Youth-Onset Schizophrenia

Abstract: We investigated the associations of rs4680 COMT, rs6280 DRD3, and rs7322347 5HT2A with youth-onset schizophrenia in the Russian population in a case–control study, and the role of the genotype in the severity of clinical features. The association between rs7322347 and schizophrenia (p = 0.0001) is described for the first time. Furthermore, we found a link with rs6280 and rs4680 in females (p = 0.001 and p = 0.02 respectively) and with rs7322347 in males (p = 0.002). Clinical symptoms were assessed on three sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…We have shown the associations of HTR2A rs7322347 and DRD3 rs6280 with schizophrenia spectrum disorder in the case-control study. This data confirms our earlier findings (16). Despite the fact that the associations of BDNF rs6265, HTR1A rs6295, SCL6A4 rs16965628 with schizophrenia in case-control study was not found, we discovered interesting correlations between BDNF rs6265 and some features of the disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have shown the associations of HTR2A rs7322347 and DRD3 rs6280 with schizophrenia spectrum disorder in the case-control study. This data confirms our earlier findings (16). Despite the fact that the associations of BDNF rs6265, HTR1A rs6295, SCL6A4 rs16965628 with schizophrenia in case-control study was not found, we discovered interesting correlations between BDNF rs6265 and some features of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…The role of HTR2A in psychosis has also been investigated in gene association studies (13,15). Thus, the 5HT2A rs7322347 (A/T) was also associated with early-onset schizophrenia (16).…”
Section: Introductionmentioning
confidence: 99%
“…Because of their anatomical distribution in the ventral striatum [43] , their locomotor adverse effects including extrapyramidal side effects and catalepsy may be negligible [44][45][46] . For example, a 6-week RCT trial con rmed the e cacy and safety of D3 antagonists for improving acute exacerbations of schizophrenia [47] .…”
Section: Discussionmentioning
confidence: 99%
“…A single nucleotide polymorphism (SNP) in the COMT gene (rs4680) causes an amino acid change from valine (Val) to methionine (Met) at position 158 (Val158Met) with a 3-to fourfold higher enzymatic activity in the Val homozygotes in comparison with the Met homozygotes (Chen et al, 2004) that is associated with a reduction of dopamine levels in the prefrontal cortex (PFC) and the mesolimbic hypodopaminergic state (Akil et al, 2003). The COMT SNPs, especially rs4680, have repeatedly been identified as associated with schizophrenia as shown by the systematic review and metaanalysis (Gonzalez-Castro et al, 2016a, 2016b and more recent data (Ahmadi et al, 2018;Morozova et al, 2019). In this section, we show that there are conflicting results regarding the impact of COMT gene on mediating the relationship between childhood adversity and development of psychosis.…”
Section: The Catechol-o-methyltransferase (Comt) Genementioning
confidence: 99%